Bianca Bracho Perez Reading a Script for Chicana Falsa
A photograph of Bianca Bracho Perez reading a script from Chicana Falsa by Michele Serros. The picture is labeled Bianca Bracho Perez creates dimension to "Cousin Amy Patty Romero." Date and location not provided.